Estrategias comunicacionales y desarrollo rural - Contreras López, Johnny Anderson (2022)
Communication is essential in companies, organizations, in the public, private and social spheres, among others, to be more competitive and improve their productivity. Its relevance lies as a strategic component in the development of a specific territory that allows people to promote communication spaces: interact, propose new ideas and projects that they promote in order to achieve greater benefit for the organization. From this it can be seen that there are many organizations and that these in turn have a communication strategy through an innovation network at the macro-regional level and that it is necessary to strengthen them by articulating their annexes, districts and provinces that allow them to have greater development opportunities. It is urgent to know the main problems that rural communities have in relation to the lack of integration, participation and organization in their community, which implies proposing a strategy based on an organizational culture that allows them to improve their rural development. The results show that the organizations as a whole have members with limited participation, others have not actively participated in any type of organizational process, but when they have the initiative to work as a team, the organization generally has problems expressing their approval and at the time to make the decision. -make it possible for them to fulfill their obligations.